Kalye Central Mall: A feasibility study on the establishment of three-storey mall in Tondo, Manila. - Cao, Kianah D., Dela Cruz, Brad Bonard C., Enriquez, Kate Bridgette A., Mendoza, Jose Miguel G., Rebancos, Renz Joshua J. 4 0 16; 5 (2024)
DEFINITION OF THE PROJECT A Three-story mall development project with a separate e-parking lot at the back of the mall which aims to be the heartbeat of Tondo. NAME OF THE PROJECT The proposed development will be named Kalye Central by Elite Developer Consultancy, and it aims to be the heart of Tondo. Elite Developer Consultancy will propose the name of the development to be called Kalye Central. It aims to become the heart of Tondo, as it is expected that the place will serve to be a lively community center. It will contain diverse shops, restaurants, and fun activities for those residents nearby. The goal is to make it a friendly space where everybody is welcome to come together and enjoy themselves. Ultimately, Kalye Central looks forward to helping people connect and be part of their community. The term Kalye comes from the Tagalog meaning street, which clearly shows how this mall would be a very popular gathering place for everybody. This shows street culture alive, which is an important component of Filipino life. The design of the mall will make it easy to visit and have a fun environment with lots of activities. The excitement in that atmosphere will make people talk and share experiences with each other. Kalye Central is a social place that will buzz with the energy of the community. The word Central underlines how important the mall will be in Tondo, which is really known for its rich history and culture. Kalye Central is going to fill many of the needs with shopping, dining, and entertainment under one roof. It hopes to create a lot of opportunities for people to be connected and establish relationships with others. A central place will give its residents something more than a place to shop; it will help them feel part of the community. Overall, Kalye Central represents the heart of the project and pays homage to local culture and traditions. Therefore, bringing these elements together means an important addition to the life of Tondo: this is what Kalye Central has in store- a very inviting space wherein people will be able to enjoy their shopping, dining, and socialization needs. In order to raise the standards of local living, it seeks to design a place where everybody seems to fit. As part of the focus on the community, Kalye Central has always shown and continues to respect culture while creating this special place for each person.
Feasibility Study: (Bachelor of Science in Real Estate Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2